Kegiatan Lomba Mewarnai sebagai Wadah Melatih Kreativitas Siswa Sekolah Dasar Kelas Rendah - Zulvia Misykah; Dewi Sartika Panggabean; Dinda Widyastika; Sintia Siallagan (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
Learning activities at the lower elementary school level are a process of preservation from kindergarten to elementary school level, in this case the learning principle applied in the lower grades is learning while playing. Activities that stimulate creativity either directly or embedded in other learning activities. One activity that can stimulate creativity is drawing and coloring. Coloring can increase students' imagination and concentration. Students are expected to be able to choose and combine colors correctly between their imagination and real objects. In the activity of coloring a picture, students will also be measured on how neat and clean the results are. Coloring will create a fun learning process. This research aims to measure how creative students are through coloring competition activities. The research method used is a qualitative method with data collection through observation, interviews and documentation. From the results of research that increases creativity through drawing and coloring activities above, it is clear that students will be more easily interested in playing activities and will be interested in colors. This coloring activity can make students express their thoughts and imagination.